Establishment of optimal QuEChERS conditions of various food matrices for rapid measurement of heterocyclic amines in various foods. (30th June 2022) - Chiang, Chow-Feng; Liao, Po-Lin; Hsu, Kuo-Chiang; Shen, Jung-Yu; Lin, Jau-Tien; Yang, Deng-Jye
Highlights: QuEChERS conditions were established to extract 21 HAs from various foods. The HAs determination conditions had good accuracy, repeatability and precision. HAs contents of popular food products sold in the Taiwan market were determined. Cooking methods and food consumption affect the dietary intake of HAs. The intake of HAs in plant-based protein foods also needs attention. Abstract: The optimal conditions for QuEChERS (quick, easy, cheap, effective, rugged and safe) with superior performance were established to rapidly extract 21 heterocyclic amines (HAs) from 9 categories of food matrices including meat and poultry, eggs, soy beans and products, composite foods, fish and seafood, grains, beer, dairy foods, and coffee. The QuEChERS conditions and the developed ultra-high performance liquid chromatography-tandem mass spectrometry analysis conditions were then applied to the determination of HAs in popular food products sold in the Taiwan market. The conditions comply with the food chemical analysis specifications of Taiwan Food and Drug Administration. Coffee products and braised products that require a longer cooking time contained relatively high content of HAs (mainly Harman and Norharman), and their consumption is relatively high resulting in relatively high intake of HAs from these products. The dietary intake of HAs in plant-based protein food products should also be of concern.